Characterization of cAMP‐phosphodiesterase activity in bovine seminal plasma. (27th August 2016) - Bergeron, A.; Aragon, J. P.; Guillemette, C.; Hébert, A.; Sullivan, R.; Blondin, P.; Richard, F. J.
Summary: The second messenger cyclic adenosine monophosphate (cAMP) has a central role in sperm physiology. Extracellular cAMP can be sequentially degraded into 5′AMP and adenosine by ecto‐phosphodiesterases (ecto‐PDE) and ecto‐nucleotidases, a phenomenon called extracellular cAMP‐adenosine pathway. As cAMP‐adenosine pathway is involved in sperm capacitation, we hypothesize that extracellular PDEs are functionally present in seminal plasma. Exclusively measuring cAMP‐PDE activity, total activity in bovine seminal plasma was 10.1 ± 1.5 fmoles/min/μg. Using different family‐specific PDE inhibitors, we showed that in seminal plasma, the major cAMP‐PDE activity was papaverine sensitive (47.5%). These data support the presence of PDE10 in bovine seminal plasma and was further confirmed by western blot. In epididymal fluid, total cAMP‐PDE activity was 48.2 ± 14.8 fmoles/min/μg and we showed that the major cAMP‐PDE activity was 3‐isobutyl‐methylxanthine insensitive and thus ascribed to PDE8 family. PDE10A mRNAs were found in the testis, epididymis, and seminal vesicles. cAMP‐PDE activity is present in bovine seminal plasma and epididymal fluid. The results suggest a role for ecto‐PDEs present in those fluids in the signaling pathways involved in sperm functions.